Development of non-metallic diamond anvil cell and quantum oscillation measurement of CePt2ln7 in a pulsed-magnet. (18th March 2015) - Miyake, Atsushi; Kohama, Yoshimitsu; Ohta, Shunpei; Hirose, Yusuke; Settai, Rikio; Matsubayashi, Kazuyuki; Uwatoko, Yoshiya; Matsuo, Akira; Kindo, Koichi; Tokunaga, Masashi
Abstract: In order to combine the extreme conditions of high pressure and magnetic field, we have developed a non-metallic diamond anvil cell to avoid Joule-heating in a pulsed-magnetic field. Although the cell is deformed with loading, a maximum pressure of 8.5 GPa can be applied. Quantum oscillation measurements using tunnel diode oscillator have been performed for heavy fermion antiferromagnet CePt2 In7 in a pulsed field and at ambient pressure. The detail of the pressure cell and field-induced Fermi surface changes of CePt2 In7 are discussed.